Personal Identity and Science: the genetic approach regarding the case of appropriated children during the most recent Argentinian dictatorship from a pluralistic perspective - Córdoba, Mariana (2020)
Fil: Córdoba, Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de Filosofía "Doctor Alejandro Korn". Buenos Aires, Argentina.